Doctrina perpetua guides on clinical surgery - Diganta Kumar Das; Saw Aung; Win, Min Thein; Lim Ze Shun; Rokeshwar Hari Dass (R & S Publishing House, 2013)
It is a guide to clinical surgery no where else seen in Malaysia as it incorporates vast amount of knowledge from leading textbooks of surgery blended with the rich experience of our distinguished professors who have also completed their MRCS